Foliar application of salicylic acid inhibits the cadmium uptake and accumulation in lettuce (Lactuca sativa L.) - Tang, Wen; Liang, Le; Xie, Yongdong; Li, Xiaomei; Lin, Lijin; Huang, Zhi; Sun, Bo; Sun, Guochao; Tu, Lihua; Li, Huanxiu; Tang, Yi (Frontiers in Plant Science, 2023)
Salicylic acid (SA) is a multi-functional endogenous phytohormone implicated in the growth, development, and metabolism of many plant species. This study evaluated the effects of different concentrations of SA (0, 25, 100, 200, and 500 mg/L) on the growth and cadmium (Cd) content of lettuce (Lactuca sativa L.) under Cd stress. The different concentrations of SA treatments were administered through foliar application. Our results showed that 100-200 mg/L SA significantly increased the plant height and biomass of lettuce under Cd stress. When SA concentration was 200 mg/L, the plant height and root length of lettuce increased by 19.42% and 22.77%, respectively, compared with Cd treatment alone. Moreover, 200 mg/L and 500mg/L SA concentrations could reduce peroxidase (POD) and superoxide dismutase (SOD) activities caused by Cd stress. When the concentration of exogenous SA was 500 mg/L, the POD and SOD activities of lettuce leaves decreased by 15.51% and 19.91%, respectively, compared with Cd treatment. A certain concentration of SA reduced the uptake of Cd by the lettuce root system and the transport of Cd from the lettuce root system to shoots by down-regulating the expression of Nramp5, HMA4, and SAMT, thus reducing the Cd content of lettuce shoots. When the concentration of SA was 100 mg/L, 200 mg/L, and 500 mg/L, the Cd contents of lettuce shoots were 11.28%, 22.70%, and 18.16%, respectively, lower than that of Cd treatment alone. Furthermore, principal component and correlation analyses showed that the Cd content of lettuce shoots was correlated with plant height, root length, biomass, antioxidant enzymes, and the expression level of genes related to Cd uptake. In general, these results provide a reference for the mechanism by which SA reduces the Cd accumulation in vegetables and a theoretical basis for developing heavy metal blockers with SA components.